Pengaruh Kompensasi, Budaya Organisasi, terhadap Motivasi Kerja dan Kinerja Pegawai - Juliningrum, Emmy; Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2013)
Human resource management is critical and the focus of many organizations in achieving a competitive advantage. Based on previous studies that assessed the effect of employee performance has an impact on organizational culture, compensation, and employee motivation. From these studies need to be tested further with the addition / change of variables, among others, the effect of compensation on work motivation and performance, organizational culture on work motivation and performance of employees, through an empirical study of an administrative officer at UB PTIIK . From the results of this study concluded that the compensation has not been able to contribute to work motivation and performance. However, cultural organizations such as the application of the rules given employee influence on employee motivation PTIIK UB that will make a positive contribution to the performance of employees .